Exercise and Caloric Restriction Alter the Immune System of Mice Submitted to a High-Fat Diet. (13th March 2013) - Wasinski, Frederick; Bacurau, Reury F. P.; Moraes, Milton R.; Haro, Anderson S.; Moraes-Vieira, Pedro M. M.; Estrela, Gabriel R.; Paredes-Gamero, Edgar J.; Barros, Carlos C.; Almeida, Sandro S.; Câmara, Niels O. S.; Araujo, Ronaldo C.
Abstract : As the size of adipocytes increases during obesity, the establishment of resident immune cells in adipose tissue becomes an important source of proinflammatory mediators. Exercise and caloric restriction are two important, nonpharmacological tools against body mass increase. To date, their effects on the immune cells of adipose tissue in obese organisms, specifically when a high-fat diet is consumed, have been poorly investigated. Thus, after consuming a high-fat diet, mice were submitted to chronic swimming training or a 30% caloric restriction in order to investigate the effects of both interventions on resident immune cells in adipose tissue. These strategies were able to reduce body mass and resulted in changes in the number of resident immune cells in the adipose tissue and levels of cytokines/chemokines in serum. While exercise increased the number of NK cells in adipose tissue and serum levels of IL-6 and RANTES, caloric restriction increased the CD4+/CD8+ cell ratio and MCP-1 levels. Together, these data demonstrated that exercise and caloric restriction modulate resident immune cells in adipose tissues differently in spite of an equivalent body weight reduction. Additionally, the results also reinforce the idea that a combination of both strategies is better than either individually for combating obesity.